Renal osteodystrophy in nondialysed adolescents. Long-term treatment with 1alpha-hydroxycholecalciferol. Issue 6 (June 1977) - Kanis, J A; Henderson, R G; Heynen, G; Ledingham, J G; Russell, R G; Smith, R; Walton, R J
Abstract : The effects of small oral doses (1-2 microgram/day) of 1alpha-hydroxycholecalciferol, given for 1 to 2 years, have been examined in four nondialysed adolescents with chronic renal failure and bone disease. Treatment increased calcium retention and plasma calcium, and decreased plasma levels of alkaline phosphatase, hydroxyproline, and immunoreactive parathyroid hormone. X-ray abnormalities of bone regressed, and 2 patients underwent successful surgical correction of knock-knees; bone histology in these 2 was normal at the time of operation. 2 patients developed hypercalcaemia which promptly reversed when 1alpha-hydroxycholecalciferol was withdrawn. In one patient treatment was initially successful, but later there was biochemical, radiographic, and histological evidence of relapse. Long-term treatment of such patients with 1alpha-hydroxycholecalciferol may be effective and facilitate the surgical correction of deformities, but this is not invariable. Toxic effects are similar to those of vitamin D itself, but are more readily reversible.